Modified polyphenylene ether resin, preparation method therefor, and resin composition including the same

JP2025021429AActive Publication Date: 2025-02-13NANYA PLASTICS CORP

Patent Information

Application Number
JP2024109423
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2024-07-08
Publication Date
2025-02-13
Estimated Expiration
2044-07-08

AI Technical Summary

Benefits of technology

【0009】 以上のように、本発明の変性ポリフェニレンエーテル樹脂は、作製が比較的簡単であり、電子部品または電子製品(例えば、回路板または銅張積層板)に適用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021429000001_ABST
    Figure 2025021429000001_ABST
Patent Text Reader

Abstract

To provide a modified polyphenylene ether resin that can be applied to electronic components or electronic products (e.g., circuit boards or copper clad laminates), and a preparation method therefor.SOLUTION: A modified polyphenylene ether resin has a structure represented by Formula 1, where R1-R8 are each selected from a hydrogen group or a C1-C6 alkyl group, P1-P4 are each selected from a single bond or a ketone group, Q1-Q4 are each selected from a benzene ring group, a styryl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methyl vinyl group, a naphthalene ring group, or hydrogen, and X is a linking group selected from a single bond or the following chemical formula.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to modified resins and methods for making the same, and in particular to modified polyphenylene ether resins and methods for making the same. [Background technology]

[0002] With the widespread adoption of 5th generation mobile networks (5G), the printed circuit board (PCB) industry is moving towards faster and higher frequency boards, which is also driving the continuous development and improvement of copper clad laminate (CCL) materials. Copper clad laminates are typically composed of copper foil, glass fiber cloth, and resin, with polyphenylene ether resin being a commonly used insulating material. Summary of the Invention [Problem to be solved by the invention]

[0003] However, industrial polyphenylene ether has a large molecular weight and a high viscosity, which may reduce the quality and / or production rate of the produced copper-clad laminate. Moreover, it is difficult to adapt the corresponding specifications to meet various requirements. Therefore, modifying polyphenylene ether resin (e.g., modifying terminal functional groups, adjusting molecular weight and distribution) to facilitate the production of copper-clad laminate and maintain the high quality of the obtained product is currently an important research topic in this field. [Means for solving the problem]

[0004] The present invention provides a modified polyphenylene ether resin and a process for producing the same, as well as a resin composition containing the modified polyphenylene ether resin.

[0005] The method for preparing the modified polyphenylene ether resin of the present invention is as follows: provide an unmodified polyphenylene ether; react the unmodified polyphenylene ether with a phenolic compound and a radical initiator to obtain a corresponding product; and subject the product to alkali washing and solvent recrystallization to obtain a modified polyphenylene ether resin.

[0006] The modified polyphenylene ether resin of the present invention has a structure represented by formula (1) in this specification.

[0007] The resin composition of the present invention contains the above-mentioned modified polyphenylene ether resin.

[0008] The electronic component of the present invention includes a film layer formed from the above-described resin composition. Effect of the Invention

[0009] As described above, the modified polyphenylene ether resin of the present invention is relatively easy to prepare and can be applied to electronic components or electronic products (for example, circuit boards or copper-clad laminates). [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic flow chart of a method for making a modified polyphenylene ether resin according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the following detailed description, for purposes of explanation and not limitation, exemplary embodiments disclosing specific details are described to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to those skilled in the art that the present invention may be practiced in other embodiments that differ from the specific details disclosed herein. Also, descriptions of well-known devices, methods, and materials may be omitted so as not to obscure the description of the various principles of the present invention.

[0012] Ranges expressed herein can be understood as from "about" a particular value to "about" another particular value, and therefore can be directly stated as a particular value and / or to another particular value. When a range is expressed, another embodiment includes from the particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation using the antecedent "about," it is understood that such particular value forms another embodiment. For example, when a value is expressed using the antecedent "about," it can be directly stated as the particular value. Moreover, when a value is expressed using the antecedent "about," it can be within ±3% of the value, and even within ±1% of the value. It should be further understood that each endpoint of a range is expressly related to or independent of the other endpoint.

[0013] As used herein, non-limiting terms (e.g., "may," "can," "for example," or other similar terms) refer to optional or selective implementation, inclusion, addition, or presence.

[0014] Here, a derivative of a compound can involve replacing a non-reactive hydrogen atom in the compound with an isotope or a non-reactive alkyl group having 1 to 5 carbon atoms (also referred to as C1 to C5).

[0015] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. It should be further understood that terms (e.g., those defined in commonly used dictionaries) should be interpreted to have a meaning consistent with their meaning in the relevant technical context, and should not be interpreted in an idealized or overly formal sense unless expressly defined herein.

[0016] Referring to Figure 1, the method for preparing a modified polyphenylene ether resin can include the following steps: Step S10: Provide an unmodified polyphenylene ether; Step S20: Modify the polyphenylene ether by reacting it with a phenol compound and a radical initiator; Step S30: Purify the reaction product by alkali washing and solvent recrystallization; Step S40: Obtain a modified polyphenylene ether.

[0017] <Modification of polyphenylene ether resin>

[0018] In one embodiment, the corresponding product can be obtained or produced by appropriately reacting an unmodified polyphenylene ether, a phenolic compound, and a radical initiator to carry out the corresponding modification.

[0019] In one embodiment, the unmodified polyphenylene ether may be a polyphenylene ether in which the corresponding phenyl group is substituted with only hydrogen or with an alkyl group having 1 to 5 carbon atoms (also referred to as C1 to C5). For example, the unmodified polyphenylene ether may be poly(2,6-dimethyl-1,4-phenylene ether) (CAS number: 25134-01-4), but the present invention is not limited thereto.

[0020] In one embodiment, the phenolic compound includes, for example, a bisphenol compound. In one embodiment, the bisphenolic compound includes, for example, bisphenol A (BPA), tetramethyl bisphenol (TMBP), tetramethyl bisphenol A (TMBPA), tetramethyl bisphenol F (TMBPF), bisphenol S (BPS), dicyclopentadiene bisphenol (e.g., DCPD-DIDMP, see chemical formula below), or a derivative thereof. [ka]

[0021] In one embodiment, the phenol compound includes, for example, a tetraphenol compound. In one embodiment, the tetraphenol compound includes, for example, 1,1,2,2-tetrakis(p-hydroxyphenyl)ethane (TPE, CAS number: 7727-33-5), or a derivative thereof.

[0022] In one embodiment, the radical initiator may include, for example, a peroxide, and preferably, the radical initiator may be a peroxide having a corresponding benzene ring. In one embodiment, the radical initiator may include benzoyl peroxide (BPO) or a derivative thereof (e.g., benzoyl peroxide having alkyl substitution). The above or below "alkyl substitution" may be an alkyl substitution in which at least one hydrogen is replaced with an alkyl group having 1 to 5 carbon atoms (also referred to as C1 to C5).

[0023] In one embodiment, the reaction of unmodified polyphenylene ether, phenolic compound, and radical initiator as products may be similar to a rearrangement reaction. The reaction mechanism may include a radical initiator forming radicals in an appropriate manner (e.g., heating). The radicals can then attack the ends of the phenolic compound to form corresponding radicals, and / or the radicals can attack the ends of the polyphenylene ether to form corresponding radicals. The reaction between the polyphenylene ether having terminal radicals and the phenolic compound having terminal radicals can be terminated by the mutual reaction / combination of the radicals to form a corresponding molecule / polymer having at least two hydroxyl groups. The above-mentioned radicals can also react with the benzene rings of the polyphenylene ether and / or structures thereon, thereby shortening the chain length of the polyphenylene ether and correspondingly reducing the molecular weight of the polyphenylene ether. Thus, in the above-mentioned reaction, the relationship between the polyphenylene ether and the radical initiator can be related to the molecular weight or polydispersity index (PDI) of the product. For example, when the ratio of radical initiator is high (e.g., high molar amount), the product may have a low molecular weight and / or a high polydispersity index, and conversely, when the ratio of radical initiator is low (e.g., low molar amount), the product may have a high molecular weight and / or a low polydispersity index. Polydispersity index, also called molecular weight distribution, refers to the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (i.e., Mw / Mn).

[0024] In one embodiment, the equivalent of the radical initiator is about 0.05 to about 2 times the phenol equivalent of the phenol compound. That is, the phenol equivalent of the phenol compound: the equivalent of the radical initiator ≈ 100:5 to 100:200. In this way, the average number of hydroxyl groups per molecule of the modified polyphenylene ether in the modified polyphenylene ether obtained after the reaction is about 2.0 or more.

[0025] In one embodiment, the equivalent of the radical initiator is preferably about 0.1 to about 1.5 times the phenol equivalent of the phenol compound, that is, the phenol equivalent of the phenol compound:the equivalent of the radical initiator is 100:10 to 100:150.

[0026] In one embodiment, the equivalent weight of the radical initiator may preferably be less than the phenol equivalent weight of the phenol compound, thus reducing the possibility of side reactions (which, however, does not mean that they can be completely avoided under natural conditions of chemical reactions).

[0027] In one embodiment, the phenol equivalent of the phenol compound is more preferably about 1.5 to about 20 times the equivalent of the radical initiator. In one embodiment, the phenol equivalent of the phenol compound is more preferably 1.5 or more times (e.g., about 1.75 times, about 1.8 times, or about 2 times) to about 10 times the equivalent of the radical initiator.

[0028] In one embodiment, a catalyst can be further added (although the present invention is not limited thereto). The catalyst can increase the reaction rate of the rearrangement reaction. The catalyst can be added together with the phenol compound. The catalyst can include a water-soluble catalyst suitable for dissolving in water, such as, for example, a tertiary amine, a quaternary ammonium salt, a phosphate, or a combination thereof. For example, the catalyst may be a tetraalkylammonium halide (e.g., tetramethyl ammonium chloride (TMAC), CAS number: 75-57-0), tetraethyl ammonium chloride (TEAC), CAS number: 56-34-8), tetramethyl ammonium bromide (TMAB), CAS number: 64-20-0, tetraethyl ammonium bromide (TEAB), CAS number: 71-91-0), tetrapropyl ammonium bromide (TPAB), CAS number: 1941-30-6, tetrabutyl ammonium bromide (TBAB), CAS number: 1643-19-2), benzyl alkyl ammonium halide (e.g., benzyl trimethyl ammonium chloride, The catalyst may include benzyltriethylammonium chloride (BTMAC, CAS number: 56-93-9), benzyltriethylammonium chloride (BTEAC, CAS number: 56-37-1), or benzyldimethyldecylammonium chloride (CAS number: 965-32-2). In one embodiment, based on the unmodified polyphenylene ether used in the reaction, the weight of the catalyst added is about 1 wt % or less of the weight of the unmodified polyphenylene ether used in the reaction.

[0029] In one embodiment, the average number of hydroxyl groups per modified polyphenylene ether molecule can be estimated by dividing the total molar amount of hydroxyl groups by the total molar amount of modified polyphenylene ether molecules (i.e., total molar amount of hydroxyl groups ÷ total molar amount of modified polyphenylene ether molecules). The total molar amount of hydroxyl groups can be determined by commonly used standards for standardization of hydroxyl number (e.g., ISO 4629-2:2016, ASTM D1959, GB / T 12008.3, and CNS 6681, but the present invention is not limited thereto). The total molar amount of polymer molecules can be converted by measuring the corresponding average molecular weight using gel permeation chromatography (GPC).

[0030] In one embodiment, the above-mentioned modification reaction can be carried out in a hydrophobic or lipophilic solvent. In one embodiment, the modification reaction can be carried out in toluene, xylene, or a co-solvent thereof.

[0031] In one embodiment, the above-described denaturation reaction can be carried out in an environment above room temperature (e.g., above 25° C.). In one embodiment, the reaction can be carried out in an environment at about 80° C. or higher.

[0032] In one embodiment, the above-mentioned modification reaction can be carried out in an environment below the boiling point temperature of the corresponding solvent.

[0033] In one embodiment, the above-mentioned modification reaction can be carried out for about 0.5 hours to 6 hours. In one embodiment, the above-mentioned modification reaction can be carried out for about 1 hour to 5 hours. In one embodiment, the above-mentioned modification reaction can be carried out for about 2 hours to 4 hours. In one embodiment, the above-mentioned modification reaction can be carried out for about 3 hours.

[0034] In one embodiment, the modified polyphenylene ether after the reaction can be further washed with an alkali. In this way, the phenol equivalent of the modified polyphenylene ether can be increased. In one embodiment, after the modified polyphenylene ether after the reaction is washed with an alkali, the average number of hydroxyl groups per molecule of the modified polyphenylene ether can be made larger than 2.2.

[0035] In one embodiment, the above-mentioned alkaline cleaning can be performed using a corresponding alkaline solution. In one embodiment, the alkaline solution can include a solution containing an alkali metal ion or an alkaline earth metal ion, and preferably includes a solution containing an alkali metal ion. Cations with a valence of +3 or more may cause undesirable side reactions. For example, the alkaline solution can include sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, sodium alkoxide (e.g., sodium methoxide (MeONa), sodium ethoxide (EtONa), sodium propoxide, sodium butoxide), potassium alkoxide (e.g., potassium methoxide (MeOK), potassium ethoxide (EtOK), potassium propoxide, potassium butoxide), or mixtures thereof, which can be dissolved in a suitable solvent (e.g., water, alcohol, alcohol-water mixture).

[0036] In one embodiment, the alkali equivalent of the alkaline solution used in the alkaline cleaning may be equal to about 10 wt % to about 60 wt % aqueous sodium hydroxide solution.

[0037] In one embodiment, the alkaline washing step described above can be carried out in an environment above room temperature (e.g., above 25° C.). In one embodiment, the reaction can be carried out in an environment at about 40° C. or higher.

[0038] In one embodiment, the above-mentioned alkaline washing step can be carried out in an environment below the boiling point temperature of the corresponding solvent.

[0039] In one embodiment, the above-mentioned alkaline washing step can be carried out for about 0.5 to 4 hours. In one embodiment, the above-mentioned modification reaction can be carried out for about 0.5 to 3 hours. In one embodiment, the above-mentioned modification reaction can be carried out for about 1 to 2 hours.

[0040] In one embodiment, after the above-mentioned modified polyphenylene ether molecule is formed, the unreacted or unreactive large molecular polyphenylene ether can be removed by solvent purification and / or recrystallization. For example, compared with the modified polyphenylene ether molecule having a molecular weight of about 20,000 mole / g, the unreacted or unreactive large molecular polyphenylene ether having a molecular weight of 40,000 or more may have low solubility in some low polarity solvents (e.g., tetrahydrofuran, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone). Therefore, the unreacted or unreactive large molecular polyphenylene ether can be precipitated and removed by adding the above-mentioned low polarity solvent. Also, the corresponding high polarity solvent (e.g., methanol, ethanol, or isopropanol) may be added to recrystallize the modified polyphenylene ether. In this way, the purity and / or quality of the modified polyphenylene ether can be improved.

[0041] In one embodiment, a modified polyphenylene ether having a number average molecular weight (Mn) of about 500 g / mol to 4,000 g / mol can be obtained by the above-mentioned solvent purification method and recrystallization, and the polydispersity index (PDI) of the modified polyphenylene ether is about 2.5 or less.

[0042] In one embodiment, a modified polyphenylene ether having a number average molecular weight (Mn) of about 1,000 g / mol to 3,000 g / mol can be obtained by the above-mentioned solvent purification method and recrystallization, and the polydispersity index (PDI) of the modified polyphenylene ether is preferably about 1.8 or less.

[0043] In one embodiment, the solvent used for recrystallization can include toluene, xylene, tetrahydrofuran (THF), methyl ethyl ketone (MEK), cyclohexanone, methyl isobutyl ketone (MIBK), or a co-solvent thereof.

[0044] In one embodiment, the modified polyphenylene ether can be represented by the following formula (1):

[0045] [ka]

[0046] In formula (1), k is an integer equal to or greater than 0. i, i', j, and j' may be the same as or different from one another, and i and j may each be an integer from 0 to 200, and i' and j' may each be an integer from 1 to 200. Furthermore, the value of i+i'+j+j'+k is 2 to 400.

[0047] In formula (1), k is preferably 0 or 1, and i, i', j, and j' may be the same or different and may each be an integer of 1 to 200. In addition, the value of i+i'+j+j'+k is preferably 4 to 200.

[0048] In formula (1), R1 to R8 may be the same or different and may each be selected from a hydrogen group or an alkyl group having 1 to 6 carbon atoms (also referred to as C1 to C6).

[0049] In formula (1), P1 to P4 may be the same or different and each may be selected from a single bond (-) or a ketone group (see the chemical formula below). [ka]

[0050] In formula (1), Q1 to Q4 may be the same or different and can be selected from a benzene ring group, a styryl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthalene ring group, or hydrogen.

[0051] In formula (1), X can be a single bond (-) or selected from the following linking groups: [ka]

[0052] In one embodiment, after the above-mentioned solvent purification and recrystallization, the ratio of large molecular weight polyphenylene ether having a molecular weight of 20,000 g / mol or more may be essentially 1.5 wt % or less, and preferably about 1.0 wt % or less, based on the total weight of the product after drying.

[0053] In one embodiment, the number average molecular weight (Mn) of the modified polyphenylene ether resin may be about 500 g / mol to 4,000 g / mol, and preferably about 1,000 g / mol to 3,000 g / mol.

[0054] In one embodiment, the dispersity index of the modified polyphenylene ether resin is about 2.5 or less, and preferably about 1.8 or less.

[0055] In one embodiment, the modified polyphenylene ether resin has a hydroxyl equivalent of about 1,300 g / eq or less, and the corresponding number of hydroxyl groups per molecule is about 2.0 to 4.0.

[0056] <Applications of modified polyphenylene ether resin>

[0057] The modified polyphenylene ether resin represented by formula (1) is suitable for application to electronic products.

[0058] The modified polyphenylene ether resin represented by formula (1) can have lower dielectric properties, higher glass transition temperature (Tg), better heat resistance, and / or better fluidity, making it suitable for application in electronic products.

[0059] The modified polyphenylene ether resin represented by formula (1) is easily soluble in common organic solvents (eg, toluene or methyl ethyl ketone (MEK)), making it convenient to use.

[0060] In one embodiment, the modified polyphenylene ether resin represented by Formula (1) in electronic applications exhibits better heat resistance, higher glass transition temperature, and / or better flowability compared to other known resins used in electronic applications.

[0061] In one embodiment, the modified polyphenylene ether resin represented by formula (1) can exhibit better heat resistance, higher glass transition temperature, and better flowability when applied to electronic products compared with other known resins used in electronic products, thus making its application (e.g., application to copper-clad laminates) relatively simple.

[0062] In one embodiment, the resin composition may include the modified polyphenylene ether resin of the above-mentioned embodiment. In one embodiment, when the total weight of the resin composition is in weight percent, the modified polyphenylene ether resin is in the range of 30 weight percent (wt%) to 60 wt%, preferably about 40 wt%.

[0063] In one embodiment, the resin composition may further include a crosslinking agent. In one embodiment, when the total weight of the resin composition is 100 wt%, the crosslinking agent may be in the range of 10 wt% to 20 wt%, and preferably about 15 wt%.

[0064] In one embodiment, the addition of a crosslinking agent can improve the degree of crosslinking between the resin and / or the corresponding polymer. In one embodiment, the crosslinking agent can include an allyl group. In one embodiment, the crosslinking agent can include triallyl cyanurate (TAC), trially isocyanurate (TAIC), trimethallyl isocyanurate (TMAIC), diallyl phthalate, divinylbenzene, triallyl trimellitate, or a combination thereof.

[0065] In one embodiment, the resin composition may include a filler. In one embodiment, when the total weight of the resin composition is 100 wt%, the filler may be in the range of 5 wt% to 15 wt%, and is preferably about 10 wt%.

[0066] In one embodiment, the viscosity of the resin composition can be improved by adding inorganic filler.For example, the inorganic filler can be silicon dioxide, titanium dioxide, aluminum hydroxide, aluminum oxide, magnesium hydroxide, magnesium oxide, calcium carbonate, boron oxide, calcium oxide, strontium titanate, barium titanate, calcium titanate, magnesium titanate, boron nitride, aluminum nitride, silicon carbide, cerium oxide, or combinations thereof.

[0067] In one embodiment, the silicon dioxide added as inorganic filler can include fused or crystalline silicon dioxide.In one embodiment, considering the dielectric properties when applied to copper clad laminate, fused silicon dioxide is more preferred.

[0068] In one embodiment, the titanium dioxide added as an inorganic filler may include rutile, anatase, or brookite type titanium dioxide. In one embodiment, in consideration of the dielectric properties when applied to copper clad laminates, rutile type titanium dioxide is more preferred.

[0069] In one embodiment, the resin composition may further include a crosslinking accelerator. In one embodiment, when the total weight of the resin composition is 100 wt%, the crosslinking accelerator may be in the range of 0.5 wt% to 1.5 wt%, and preferably about 1.0 wt%.

[0070] In one embodiment, crosslinking promoters can improve system reactivity. The promoters can include catalysts and peroxides.

[0071] In one embodiment, the catalyst used as the crosslinking promoter may include 2-phenyl-1H-imidazole-1-propionitrile (2PZCN; CAS number: 23996-12-5), 1-benzyl-2-phenyl-1H-imidazole (1B2PZ; CAS number: 37734-89-7), thiabendazole (TBZ; CAS number: 148-79-8), or a combination thereof, but the present invention is not limited thereto.

[0072] In one embodiment, the peroxide as the crosslinking promoter is tert-butylcumyl peroxide, dicumyl peroxide (DCP), benzoyl peroxide, BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di(tert-butylperoxyisopropyl)benzene, Luperox® F series peroxide preparations (e.g., 1,3(4)-bis(tert-butylperoxyisopropyl)benzene (1,3(4) -bis(tert-butylperoxyisopropyl)benzene), see the chemical formula below, LuF), or combinations thereof, but the present invention is not limited thereto. [ka]

[0073] In one embodiment, the resin composition may further include a flame retardant. In one embodiment, when the total weight of the resin composition is 100 wt%, the flame retardant may be in the range of 5 wt% to 15 wt%, and is preferably about 10 wt%.

[0074] In one embodiment, the flame resistance or flame retardancy of the resin composition can be improved by adding a flame retardant. Here, "flame resistance" or "flame retardancy" means that the object (e.g., a film, layer, or structure) to which it refers can meet the flame retardancy criteria of a standard test method. For example, in the UL94 plastic flammability standard for Test for Flammability of Plastic Materials for Parts in Devices and Appliances issued by UL (Underwriters Laboratories) of the United States, the standard value is at least HB grade.

[0075] In one embodiment, the flame retardant may include a brominated flame retardant, a phosphorus-based flame retardant, or a combination thereof, although the invention is not limited thereto.

[0076] In one embodiment, the brominated flame retardant can include Saytex BT93W (ethylene bistetrabromophthalimide) flame retardant, Saytex BT93, Saytex 120 (tetradecabromodiphenoxy benzene) flame retardant, Saytex 8010 (ethane-1,2-bis(pentabromophenyl)) flame retardant, Saytex 102 (decabromo diphenoxy oxide) flame retardant, or combinations thereof, manufactured by Albemarle Corporation, USA.

[0077] In one embodiment, the phosphorus-based flame retardant may include sulfosuccinic acid ester, phosphazene, ammonium polyphosphate, melamine polyphosphate, melamine cyanurate, or a combination thereof. For example, triphenyl phosphate (TPP), resorcinol bis(diphenyl phosphate) (RDP), bisphenol A bis(diphenyl phosphate) (BPAPP), resorcinol bis(diphenyl phosphate) (e.g., CR-733S manufactured by Nippon Daihachi Chemical Industry Co., Ltd.), 1,3-phenylene trax(2,6-dimethylphenyl) phosphate ester (e.g., PX-200 manufactured by Nippon Daihachi Chemical Industry Co., Ltd.), SPB-100 phosphorus-based flame retardant manufactured by Nippon Otsuka Chemical Co., Ltd., or a combination thereof.

[0078] In one embodiment, a resin composition containing the modified polyphenylene ether resin according to one embodiment of the present invention can be used in the manufacture of electronic components (such as, but not limited to, copper-clad laminates or printed circuit boards).

[0079] In one embodiment, a resin composition including the modified polyphenylene ether resin in one embodiment of the present invention is suitable for forming an insulating film for electronic products, and its application to electronic products can have specifications such as a dielectric constant (Dk) of about 4.0 or less (e.g., about 3.3 to 4.0), a dissipation factor (Df) of about 0.0050 or less (e.g., about 0.0035 to 0.0050), a glass transition temperature (Tg) of about 210°C to 235°C, a peel strength of greater than about 6.0 lb / in (e.g., even 6.5 lb / in or more), and / or a water absorption of about 0.5% or less (e.g., a 2-hour water absorption of about 0.5% or less).

[0080] Most of the commercially available resins used in the manufacture of copper-clad laminates (e.g., SA-9000 resin from Sabic, but the present invention is not limited thereto) are made by oxidative polymerization. However, the above-mentioned oxidative polymerization method requires the introduction of oxygen. In the process of introducing oxygen, the flow rate, speed, and / or concentration of oxygen must be controlled to prevent the possibility of violent oxidation reactions (e.g., combustion, flashover, or explosion) caused by the coexistence of the solvent and oxygen. In addition, a reaction tank suitable for the above-mentioned oxidative polymerization must be equipped with a gas detector, a fire protection device, and / or an explosion prevention device, which accordingly increases the production cost. In addition, the oxidative polymerization method often requires the addition of a metal catalyst (mainly a metal or transition metal with a valence of +3 or more). Separating the metal catalyst from the product usually requires purification, which makes the corresponding reaction process more complicated. In addition, the oxidative polymerization method is not suitable for customized modification because it needs to be carried out in a specific environment (e.g., a specific solvent). For the above reasons, the modified polyphenylene ether resin in one embodiment of the present invention provides a simpler manufacturing process than commercially available resins used in the manufacture of copper-clad laminates.Furthermore, the modified polyphenylene ether resin in one embodiment of the present invention is suitable for the manufacture of copper-clad laminates, and / or the copper-clad laminates manufactured therewith meet general standards.

[0081] <Manufacturing of copper-clad laminates>

[0082] The modified polyphenylene ether resin of the above embodiment can be dissolved in a suitable solvent and mixed with other components to form a resin varnish, which can be used to prepare a copper-clad laminate using known methods. For example, the resin composition of the above embodiment can be dissolved in a suitable solvent to form a resin varnish, which can be used to manufacture a copper-clad laminate.

[0083] The copper clad laminate can be manufactured as follows.

[0084] 2116 fiberglass cloth is impregnated with the above-mentioned resin varnish, and then dried for several minutes under the condition of about 170°C (including the temperature of the impregnator). By adjusting and controlling the drying time, a post-dried prepreg with a melting point viscosity of about 4,000 to 12,000 poise is obtained. Then, a lamination process is performed (details are as follows) by stacking four prepregs layer by layer between two copper foils with a thickness of about 35 μm to form a copper clad laminate of one embodiment.

[0085] The conditions / procedures for the lamination process are as follows:

[0086] Step 1: The temperature is increased from about 80° C. to about 195° C. over a period of about 0.5 hours (referred to as 85→195° C., 0.5 hours).

[0087] Step 2: Apply pressure of approximately 7 kg / cm for approximately 0.5 hours. 2 ~About 25kg / cm 2 (7→25kg / cm 2 , 0.5 hours).

[0088] Step 3: Temperature of about 195°C and about 25kg / cm 2 Laminate for approximately 2.0 hours at a pressure of 195°C / 5kg / cm 2 , 2.0 hours).

[0089] <Examples and Comparative Examples>

[0090] The present invention will be specifically described below with examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that for the sake of brevity, certain numerical values ​​in the examples or comparative examples (such as those recorded in tables) may be indicated without the modifier "about". Also, each value may include values ​​and average values ​​within the acceptable deviation range for a particular value as determined by a person skilled in the art, and may have a range of ±3% of the value, and even a range of ±1% of the value, taking into account the measurement being discussed and the particular amount of error associated with the measurement (i.e., the limitations of the measurement system).

[0091] <Preparation Examples of Modified Polyphenylene Ether Resins and Corresponding Comparative Examples>

[0092] <Example 1>

[0093] Approximately 600 grams of toluene, approximately 100 grams of commercially available polyphenylene ether (trade name: XYRON TM ) S203A, manufactured by Asahi Kasei Engineering Plastics Corporation), about 0.5 grams of tetramethylammonium chloride, and about 8.25 grams of tetramethylbisphenol A were added to a reaction vessel and heated to 90° C. to dissolve.

[0094] Next, about 3.7 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 4 portions) over a period of about 60 minutes. Continuous stirring was maintained during this process, and a constant temperature (above about 70° C., e.g., between about 70° C. and 90° C.) was maintained.

[0095] After the above-mentioned dropwise addition was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 90° C.) for about 3 hours to cause a reaction.

[0096] After the reaction, the reaction solution was subjected to alkaline washing with an appropriate amount of 20 wt% aqueous sodium hydroxide solution (for example, the total volume ratio of the aqueous sodium hydroxide solution to the reaction solution used may be about 1:1 to 1:5) at a constant temperature (about 70°C) for about 1 hour. Then, the aqueous layer was removed.

[0097] Then, tetrahydrofuran was added to the organic solvent layer after removing the aqueous layer, and unreacted or non-reactive polyphenylene ether was removed by recrystallization at about 15° C. or less. Methanol was then added to precipitate the resin, and a drying process was performed.

[0098] The number average molecular weight of the resin in Example 1 may be about 2,772 g / mol, the molecular weight distribution may be about 1.47, the hydroxyl equivalent of the resin may be about 1260 g / eq, and the number of hydroxyl groups per molecule (i.e., number average molecular weight / resin hydroxyl equivalent) may be about 2.2. Also, the ratio of the total weight of polymer monomers with a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 0.5 wt%.

[0099] <Example 2>

[0100] About 600 grams of toluene, about 100 grams of a commercially available polyphenylene ether (trade name: Zylon S202A, manufactured by Asahi Kasei Engineering Plastics Corporation), about 0.5 grams of benzyltrimethylammonium chloride, and about 11.6 grams of tetramethylbiphenol were added to a reaction vessel and heated to about 100° C. to dissolve.

[0101] Next, about 5.2 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 8 portions) over a period of about 120 minutes. Continuous stirring was maintained during this process, and a constant temperature (above about 70° C., e.g., between about 70° C. and 100° C.) was maintained.

[0102] After the above-mentioned dropping was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 100° C.) for about 3 hours to cause a reaction.

[0103] After the reaction, the reaction solution was subjected to alkaline washing with an appropriate amount of sodium methoxide at a constant temperature (about 50° C. or higher, for example, about 50° C. to 70° C.) for about 1 hour. Then, water was added for washing, and the aqueous layer was removed.

[0104] Then, methyl ethyl ketone was added to the organic solvent layer after removing the aqueous layer, and unreacted or non-reactive polyphenylene ether was removed by recrystallization at about 15° C. or less. Methanol was then added to precipitate the resin, and a drying process was performed.

[0105] The number average molecular weight of the resin in Example 2 may be about 2,320 g / mol, the molecular weight distribution may be about 1.43, the hydroxyl equivalent of the resin may be about 960 g / eq, and the number of hydroxyl groups per molecule may be about 2.4. Also, the ratio of the total weight of polymer monomers having a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 0.3 wt%.

[0106] <Example 3>

[0107] About 600 grams of xylene, about 100 grams of a commercially available polyphenylene ether (trade name: StarAir® LXR-035, manufactured by China National BlueStar (Group) Co., Ltd.), and about 20 grams of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane were added to a reaction vessel and heated to about 110° C. to dissolve.

[0108] Next, about 10 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 12 portions) over a period of about 240 minutes. Continuous stirring was maintained during this process, and a constant temperature (above about 70° C., e.g., between about 70° C. and 110° C.) was maintained.

[0109] After the above-mentioned dropping was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 110° C.) for about 3 hours to cause a reaction.

[0110] After the reaction, the reaction solution was subjected to alkaline washing with an appropriate amount of sodium methoxide at a constant temperature (about 50° C. or higher, for example, about 50° C. to 70° C.) for about 2 hours. Then, water was added for washing, and the aqueous layer was removed.

[0111] Thereafter, cyclohexanone was added to the organic solvent layer after removing the aqueous layer, and unreacted or non-reactive polyphenylene ether was removed by recrystallization at about 4° C. or less. Methanol was then added to precipitate the resin, and a drying step was performed.

[0112] The number average molecular weight of the resin in Example 3 may be about 2,124 g / mol, the molecular weight distribution may be about 1.50, the hydroxyl equivalent weight of the resin may be about 566 g / eq, and the number of hydroxyl groups per molecule may be about 3.75. Also, the ratio of the total weight of polymer monomers having a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 0.9 wt%.

[0113] <Example 4>

[0114] About 600 grams of toluene, about 100 grams of a commercially available polyphenylene ether (trade name: Zylon S203A), about 0.5 grams of tetramethylammonium chloride, and about 19 grams of tetramethylbiphenol were added to a reaction vessel and heated to 90° C. to dissolve.

[0115] Next, about 6 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 6 portions) over a period of about 120 minutes. Continuous stirring was maintained during this process, and a constant temperature (about 70° C. or higher, e.g., about 70° C. to 90° C.) was maintained.

[0116] After the above-mentioned dropwise addition was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 90° C.) for about 3 hours to cause a reaction.

[0117] After the reaction, the reaction solution was washed with an appropriate amount of 8 wt % aqueous sodium hydrogen carbonate solution at a constant temperature (about 70° C.) for about 1 hour, and then the aqueous layer was removed.

[0118] Then, methyl isobutyl ketone was added to the organic solvent layer after removing the aqueous layer, and unreacted or non-reactive polyphenylene ether was removed by recrystallization at about 25° C. or less. Then, methanol was added to precipitate the resin, and a drying process was performed.

[0119] The number average molecular weight of the resin in Example 4 may be about 1,750 g / mol, the molecular weight distribution may be about 1.60, the hydroxyl equivalent of the resin may be about 670 g / eq, and the number of hydroxyl groups per molecule may be about 2.60. Also, the ratio of the total weight of polymer monomers having a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 0.1 wt%.

[0120] <Example 5>

[0121] About 600 grams of toluene, about 100 grams of a commercially available polyphenylene ether (trade name: Zylon S202A), about 0.5 grams of tetramethylammonium chloride, and about 42 grams of tetramethylbiphenol were added to a reaction vessel and heated to 80° C. to dissolve.

[0122] Next, about 10 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 6 portions) over a period of about 120 minutes. Continuous stirring was maintained during this process, and a constant temperature (about 70° C. or higher, e.g., about 70° C.-80° C.) was maintained.

[0123] After the above-mentioned dropping was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours to cause a reaction.

[0124] After the reaction, the reaction solution was washed with an appropriate amount of 49.5 wt % aqueous sodium hydroxide solution at a constant temperature (about 70° C.) for about 1 hour, and then the aqueous layer was removed.

[0125] Then, cyclohexanone was added to the organic solvent layer after removing the aqueous layer, and unreacted or non-reactive polyphenylene ether was removed by recrystallization at about 25° C. or less. Methanol was then added to precipitate the resin, followed by a drying process.

[0126] The number average molecular weight of the resin in Example 5 may be about 1,260 g / mol, the molecular weight distribution may be about 1.5, the hydroxyl equivalent of the resin may be about 360 g / eq, and the number of hydroxyl groups per molecule may be about 3.50. Also, the ratio of the total weight of polymer monomers having a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 0.05 wt%.

[0127] <Comparative Example 1>

[0128] About 600 grams of toluene, about 100 grams of a commercially available polyphenylene ether (trade name: Zylon S202A), about 0.5 grams of tetramethylammonium chloride, and about 8 grams of tetramethylbiphenol were added to a reaction vessel and heated to 80° C. to dissolve.

[0129] Next, about 19 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 6 portions) over a period of about 120 minutes. Continuous stirring was maintained during this process, and a constant temperature (about 70° C. or higher, e.g., about 70° C.-80° C.) was maintained.

[0130] After the above-mentioned dropping was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours to cause a reaction.

[0131] After the reaction, the reaction solution was directly washed with water at a constant temperature (about 70° C.), and then the aqueous layer was removed.

[0132] Thereafter, the aqueous layer was removed, and methanol was added to the organic solvent layer to precipitate the resin, followed by a drying step.

[0133] The number average molecular weight of the resin in Comparative Example 1 may be about 1,815 g / mol, the molecular weight distribution may be about 4.50, the hydroxyl equivalent of the resin may be about 1,215 g / eq, and the number of hydroxyl groups per molecule may be about 1.5. Also, the ratio of the total weight of polymer monomers having a molecular weight of more than 20,000 g / mol to the total weight of the resin was about 6.5 wt%.

[0134] <Comparative Example 2>

[0135] About 600 grams of toluene, about 100 grams of a commercially available polyphenylene ether (trade name: Zylon S202A), about 0.5 grams of tetramethylammonium chloride, and about 6 grams of tetramethylbiphenol were added to a reaction vessel and heated to 80° C. to dissolve.

[0136] Next, about 30 grams of about 75 wt % benzoyl peroxide was added dropwise (e.g., in at least 6 portions) over a period of about 120 minutes. Continuous stirring was maintained during this process, and a constant temperature (about 70° C. or higher, e.g., about 70° C.-80° C.) was maintained.

[0137] After the above-mentioned dropping was completed, the mixture was stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours to cause a reaction.

[0138] After the reaction, the reaction solution was directly washed with water at a constant temperature (about 70° C.), and then the aqueous layer was removed.

[0139] Thereafter, the aqueous layer was removed, and methanol was added to the organic solvent layer to precipitate the resin, followed by a drying step.

[0140] The number average molecular weight of the resin in Comparative Example 2 may be about 1,292 g / mol, the molecular weight distribution may be about 3.8, the hydroxyl equivalent of the resin may be about 685 g / eq, and the number of hydroxyl groups per molecule may be about 1.9. Also, the ratio of the total weight of polymer monomers having a molecular weight exceeding 20,000 g / mol to the total weight of the resin was about 4.2 wt%.

[0141] The corresponding adjustments and results of <Example 1> to <Example 5> and <Comparative Example 1> to <Comparative Example 5> are shown in Table 1.

[0142] [Table 1]

[0143] <Evaluation method>

[0144] Specific molecular weight distribution ratio: The corresponding distribution ratio of a specific molecular weight can be estimated by integrating the corresponding molecular weight distribution curve. Take the distribution ratio with a molecular weight of 20,000 g / mol or more as an example, it can be obtained by dividing the curve integral value with a molecular weight of 20,000 g / mol or more by the curve integral value of all the molecular weight distribution.

[0145] Number average molecular weight (Mn): The modified polyphenylene ether resin was dissolved in tetrahydrofuran (THF) to prepare a test solution with a concentration of 1 wt%. The number average molecular weight of the test solution was then measured by gel permeation chromatography (GPC).

[0146] Weight average molecular weight (Mw): The modified polyphenylene ether resin was dissolved in tetrahydrofuran (THF) to prepare a test solution with a concentration of 1 wt%. The weight average molecular weight of the test solution was then measured by gel permeation chromatography (GPC).

[0147] Dispersity Index (PDI): Dispersity index was calculated by dividing the measured weight average molecular weight by the measured number average molecular weight (i.e., Mw / Mn). The smaller the PDI, the more concentrated the molecular weight distribution. Under the same or similar conditions of initial reactants, catalyst, and their corresponding amounts, the smaller the PDI, the more concentrated the molecular weight distribution, because the corresponding side reaction is less likely. Thus, a concentrated molecular weight distribution (i.e., a small PDI) represents more uniform functionality, shape, and / or structure, and the reaction / synthesis is more uniform. A concentrated molecular weight distribution (i.e., a small PDI) also indicates that the relative ratio of by-products from side reactions (e.g., large polymer molecules formed by repolymerization) may be reduced. As a result, in terms of product application, the subsequent treatment or application can be more stable, and the product quality or yield can be improved during further processing.

[0148] Hydroxyl equivalent: determined by commonly used standards (e.g., ISO4629-2:2016, ASTM E222-10, GB / T12008.3, and CNS6681, but the present invention is not limited thereto).

[0149] Number of hydroxyl groups per molecule: calculated from the corresponding hydroxyl group equivalent and the corresponding molecular weight (e.g., number average molecular weight).

[0150] As shown in Table 1, the polydispersity index (PDI; i.e., Mw / Mn) of the modified polyphenylene ether resins (which may be modified polyphenylene ether resins in one embodiment of the present invention) of <Examples 1> to <Examples 5> is lower than that of <Comparative Example 1> and <Comparative Example 2>. Therefore, the subsequent processing or application can be more stable, so that the subsequent processed products can have better quality or yield.

[0151] As shown in Table 1, compared with <Example 1> to <Example 5>, the number average molecular weights of the resins of <Comparative Example 1> and <Comparative Example 2> (i.e., may be referred to as unmodified polyphenylene ether resins, not modified polyphenylene ether resins in one embodiment of the present invention) were comparable to those of <Example 1> to <Example 5>. However, the ratio of molecules with molecular weights of 20,000 g / mol or more was high. This may be because a corresponding alkaline washing step was not performed, making it difficult or impossible to separate and remove large molecular polyphenylene ether. Therefore, the resins of <Comparative Example 1> and <Comparative Example 2> may have low subsequent applicability.

[0152] As shown in Table 1, the modified polyphenylene ether resins of Examples 1 to 5 (which may be the modified polyphenylene ether resin in one embodiment of the present invention) had a larger number of hydroxyl groups per molecule than those of Comparative Example 1 and Comparative Example 2. This may be because the method for producing the modified polyphenylene ether resin in one embodiment of the present invention includes a corresponding alkali washing step, which increases the number of hydroxyl groups per molecule.

[0153] <Examples and comparative examples of application to copper-clad laminates>

[0154] A resin varnish composition was prepared by mixing based on the composition ratio shown in Table 2, and a copper-clad laminate was prepared using the method described above.

[0155] In <Example 6> to <Example 10>, the modified polyphenylene ether used may be the modified polyphenylene ether obtained in <Example 1> to <Example 5>, respectively. In <Comparative Example 3>, the polyphenylene ether used may be a type of resin commonly used in the manufacture of general copper-clad laminates (e.g., SA-9000 resin manufactured by Sabic Corporation; that is, it may be referred to as a non-modified polyphenylene ether resin rather than the modified polyphenylene ether resin in one embodiment of the present invention). In <Comparative Example 4>, the polyphenylene ether used may be the resin of <Comparative Example 1> (that is, it may be referred to as a non-modified polyphenylene ether resin rather than the modified polyphenylene ether resin in one embodiment of the present invention).

[0156] In <Examples 6> to <Examples 10> and <Comparative Examples 3> and <Comparative Examples 4>, the crosslinking agent used was triallyl isocyanurate sold by Mitsubishi Chemical Corporation.

[0157] In <Examples 6> to <Examples 10> and <Comparative Examples 3> and <Comparative Examples 4>, the filler used was a silicon dioxide filler commercially available under the trade name 525ARI series.

[0158] In <Examples 6> to <Examples 10> and <Comparative Examples 3> and <Comparative Examples 4>, the crosslinking accelerator used was a peroxide formulation crosslinking accelerator commercially available from Arkema SA under the trade name Luperox F Series.

[0159] In <Examples 6> to <Examples 10> and <Comparative Examples 3> and <Comparative Examples 4>, the flame retardant used was a phosphorus-based flame retardant commercially available from Otsuka Chemical Co., Ltd. of Japan under the trade name SPB-100.

[0160] In <Examples 6> to <Examples 10> and <Comparative Examples 3> and <Comparative Examples 4>, about 53 parts by weight (also referred to as 53 wt %) of the resin composition (including the modified polyphenylene ether resin or unmodified polyphenylene ether resin described above, crosslinker, filler, crosslinking accelerator, and flame retardant) was mixed with about 47 parts by weight (also referred to as 47 wt %) of a solvent (toluene / methyl ethyl ketone co-solvent) to form a corresponding resin varnish composition used in the preparation of copper-clad laminates.

[0161] <Example 6>

[0162] The resin of Example 1 was olefinated with methacrylic anhydride.

[0163] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 1, about 14.7 grams of methacrylic anhydride, and about 8.9 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 85° C. for about 4 hours.

[0164] After the reaction, methanol was added to precipitate the resin, which was then washed.

[0165] After washing and drying, the resin had an acid value of about 1.44 mg KOH / g, an OH value of the residual hydroxyl groups of about 0.5 mg KOH / g, a number average molecular weight of about 2,840 g / mol, and a molecular weight distribution of about 1.45.

[0166] A resin varnish composition was prepared by mixing based on the composition ratio shown in Table 2, and a copper-clad laminate was prepared using the method described above, and then evaluated.

[0167] Specifically, in Example 6, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of the olefinated resin of Example 1, about 15 parts by weight (also referred to as 15 wt%) of a crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of a filler, about 1 part by weight (also referred to as 1 wt%) of a crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of a flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Example 6.

[0168] <Example 7>

[0169] The resin of Example 2 was olefinated with methacrylic anhydride.

[0170] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 2, about 18.7 grams of methacrylic anhydride, and about 11.5 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 90° C. for about 5 hours.

[0171] After the reaction, methanol was added to precipitate the resin, which was then washed.

[0172] After washing and drying, the resin had an acid value of about 1.34 mg KOH / g, an OH value of the residual hydroxyl groups of about 0.1 mg KOH / g, a number average molecular weight of about 2,460 g / mol, and a molecular weight distribution of about 1.41.

[0173] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0174] Specifically, in Example 7, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of the olefinated resin of Example 2, about 15 parts by weight (also referred to as 15 wt%) of a crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of a filler, about 1 part by weight (also referred to as 1 wt%) of a crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of a flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Example 7.

[0175] <Example 8>

[0176] The resin of Example 3 was olefinated with methacrylic anhydride.

[0177] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 3, about 27.2 grams of methacrylic anhydride, and about 16.6 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 95° C. for about 6 hours.

[0178] After the reaction, methanol was added to precipitate the resin, which was then washed.

[0179] After washing and drying, the resin had an acid value of about 1.2 mg KOH / g, an OH value of the residual hydroxyl groups measured by titration of about 0.7 mg KOH / g, a number average molecular weight of about 2,392 g / mol, and a molecular weight distribution of about 1.43.

[0180] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0181] Specifically, in Example 8, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of the olefinated resin of Example 3, about 15 parts by weight (also referred to as 15 wt%) of a crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of a filler, about 1 part by weight (also referred to as 1 wt%) of a crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of a flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Example 8.

[0182] <Example 9>

[0183] The resin of Example 4 was olefinated with methacrylic anhydride.

[0184] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 4, about 27.6 grams of methacrylic anhydride, and about 15.5 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 85° C. for about 6 hours.

[0185] After the reaction, methanol was added to precipitate the resin, which was then washed.

[0186] After washing and drying, the resin had an acid value of about 1.2 mg KOH / g, an OH value of the residual hydroxyl groups measured by titration of about 0.2 mg KOH / g, a number average molecular weight of about 1,955 g / mol, and a molecular weight distribution of about 1.45.

[0187] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0188] Specifically, in Example 9, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of the olefinated resin of Example 4, about 15 parts by weight (also referred to as 15 wt%) of a crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of a filler, about 1 part by weight (also referred to as 1 wt%) of a crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of a flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Example 9.

[0189] <Example 10>

[0190] The resin of Example 5 was olefinated with methacrylic anhydride.

[0191] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 5, about 51.3 grams of methacrylic anhydride, and about 27.1 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 85° C. for about 4 hours.

[0192] After the reaction, methanol was added to precipitate the resin, which was then washed.

[0193] After washing and drying, the resin had an acid value of about 1.5 mg KOH / g, an OH value of the residual hydroxyl groups measured by titration of about 0.1 mg KOH / g, a number average molecular weight of about 1,417 g / mol, and a molecular weight distribution of about 1.45.

[0194] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0195] Specifically, in Example 10, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of the olefinated resin of Example 5, about 15 parts by weight (also referred to as 15 wt%) of a crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of a filler, about 1 part by weight (also referred to as 1 wt%) of a crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of a flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Example 10.

[0196] <Comparative Example 3>

[0197] SA-9000 resin (Savic) was olefinated with methacrylic anhydride.

[0198] Specifically, about 100 grams of toluene, about 100 grams of the resin of Comparative Example 1, about 15.2 grams of methacrylic anhydride, and about 8.5 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 85° C. for about 4 hours.

[0199] After the reaction, methanol was added to precipitate and wash the resin, and then centrifugal separation was performed using toluene as a solvent to remove insoluble products (which may contain the corresponding resin).

[0200] The dried product (which may include the corresponding resin) exhibited an acid number of about 2.2 mg KOH / g, an OH number of the residual hydroxyl groups of about 0.1 mg KOH / g as determined by titration, a number average molecular weight of about 1,452 g / mol, and a molecular weight distribution of about 1.8.

[0201] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0202] Specifically, in Example 3, when the total weight of the resin composition is 100 wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40 wt%) of olefinated SA-9000 resin, about 15 parts by weight (also referred to as 15 wt%) of crosslinking agent, about 10 parts by weight (also referred to as 10 wt%) of filler, about 1 part by weight (also referred to as 1 wt%) of crosslinking accelerator, and about 10 parts by weight (also referred to as 10 wt%) of flame retardant. Furthermore, about 53 parts by weight (also referred to as 53 wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47 wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in the preparation of a copper-clad laminate in Comparative Example 3.

[0203] <Comparative Example 4>

[0204] The resin of <Comparative Example 1> was olefinated with methacrylic anhydride.

[0205] Specifically, about 100 grams of toluene, about 100 grams of the resin of Comparative Example 4, about 15.2 grams of methacrylic anhydride, and about 8.5 grams of 4-(dimethylamino)pyridine (DMAP) were added to a reaction vessel, which was filled with dry nitrogen and heated to about 85° C. for about 4 hours.

[0206] After the reaction, methanol was added to precipitate and wash the resin, and then centrifugal separation was performed using toluene as a solvent to remove insoluble products (which may contain the corresponding resin).

[0207] The dried product (which may include the corresponding resin) exhibited an acid number of about 2.2 mg KOH / g, an OH number of the residual hydroxyl groups of about 0.1 mg KOH / g as determined by titration, a number average molecular weight of about 1,452 g / mol, and a molecular weight distribution of about 1.8.

[0208] A resin varnish composition was prepared by mixing based on the compounding ratio shown in Table 2, and a copper-clad laminate was prepared using the same method as in Example 6. Evaluation was then carried out.

[0209] Specifically, in <Comparative Example 4>, when the total weight of the resin composition is 100wt%, the resin composition is composed of about 40 parts by weight (also referred to as 40wt%) of the olefinated resin of <Comparative Example 1>, about 15 parts by weight (also referred to as 15wt%) of the crosslinking agent, about 10 parts by weight (also referred to as 10wt%) of the filler, about 1 part by weight (also referred to as 1wt%) of the crosslinking accelerator, and about 10 parts by weight (also referred to as 10wt%) of the flame retardant. Furthermore, about 53 parts by weight (also referred to as 53wt%) of the resin composition was mixed with about 47 parts by weight (also referred to as 47wt%) of a solvent (toluene / methyl ethyl ketone cosolvent) to obtain a resin varnish composition used in <Comparative Example 3> for producing a copper-clad laminate.

[0210] <Examples and comparative examples of application to copper-clad laminates>

[0211] A resin varnish composition was prepared by mixing based on the composition ratio shown in Table 2, and a copper-clad laminate was prepared using the method described above.

[0212] [Table 2]

[0213] <Evaluation method>

[0214] Dynamic viscosity test

[0215] A prepreg of 2116 glass fiber cloth with a resin content (RC) of 53% (also called 2116RC53%) was used to carry out the corresponding evaluation as follows. Method: The prepreg was rubbed to generate powder, and about 0.45 grams of the powder was placed in a commercially available rheometer (e.g., TA Instruments or Hitachi) to measure the dynamic viscosity. Measurement conditions: The heating rate was about 2.5°C / min, and the measurement temperature range was 50°C to 180°C. The minimum viscosity value (unit: Pa·s), the minimum temperature having the minimum viscosity value (also called "minimum point"; unit: °C), and the corresponding temperature range (also called "width"; unit: °C) were recorded. The temperature range (also called "width"; unit: °C) represents the corresponding temperature range in which the viscosity of the resin composition is 10000 Pa·s or less. By comparing the temperature ranges, the difference in the operability of the corresponding resins can be shown. For example, a larger temperature range suggests better operability.

[0216] b.Water absorption rate

[0217] A 5 cm x 5 cm square specimen was placed in an oven at about 105°C for a suitable period of time (e.g., about 2 hours), and then the specimen was transferred to a pressure cooker. The conditions in the pressure cooker were about 2 atm x 120°C. After about 120 minutes in the pressure cooker, the water absorption was calculated by the following formula: weight difference of the specimen before and after placing in the pressure cooker ÷ initial weight of the specimen x 100%.

[0218] c. Heat resistance

[0219] The test method was to immerse the pressure cooker specimens described above in a soldering oven at 288±5°C and observe. The time required for the specimens to delaminate was recorded. Generally, if no delamination was observed within 60 minutes, it indicates that the heat resistance test was passed.

[0220] d. Peel strength

[0221] Similarly to the above method, the peel strength of the film made of the resin composition of the above formulation was measured by a universal tensile tester according to IPC-TM-650, method 2.4.8.

[0222] e. Dielectric constant (Dk)

[0223] Dielectric constant test: The test method was to bake a square copper-clad laminate test piece of about 5 cm x 5 cm, from which the copper foil had been removed, in an oven at about 105°C for about 2 hours. The thickness was measured with a thickness gauge, and then the test piece was clamped in an impedance analyzer (Agilent E4991A) to measure the dielectric constant Dk data at three points and calculate the average value.

[0224] f. Dielectric tangent (Df)

[0225] Dielectric loss tangent test: The test method was to bake a square copper-clad laminate test piece of about 5 cm x 5 cm from which the copper foil had been removed in an oven at about 105°C for about 2 hours. The thickness was measured with a thickness gauge, and then the test piece was clamped in an impedance analyzer (Agilent E4991A) to measure the dielectric loss tangent Df data at three points and calculate the average value.

[0226] g. Glass transition temperature (Tg)

[0227] The glass transition temperature (Tg) of the film made from the resin composition having the above blend was measured by a dynamic mechanical analyzer (DMA) in the same manner as described above.

[0228] <Evaluation method>

[0229] According to the experimental results in Table 2, the modified polyphenylene ether resin in one embodiment of the present invention can be used to prepare copper clad laminates. Moreover, the electrical properties and / or glass transition temperature of the prepared copper clad laminates are equal to or higher than those of traditional resins (e.g., polyphenylene ether resins used in the manufacture of common copper clad laminates).

[0230] Furthermore, Dk and Df can still satisfy the dielectric level of a typical copper-clad laminate (for example, a very low loss level of Df of 0.0030 to 0.0065).

[0231] Additionally, other properties are comparable or within corresponding standards when compared to traditional resins (e.g., polyphenylene ether resins used in the manufacture of typical copper-clad laminates).

[0232] As described above, compared with commercially available resins used in the manufacture of copper-clad laminates, the modified polyphenylene ether resin in one embodiment of the present invention provides a simpler manufacturing process.Furthermore, the modified polyphenylene ether resin in one embodiment of the present invention is suitable for the manufacture of copper-clad laminates, and / or the copper-clad laminates manufactured using the modified polyphenylene ether resin meet general standards.

[0233] Furthermore, by adjusting the preparation method and / or the corresponding ratio of the modified polyphenylene ether resin in one embodiment of the present invention, the resin composition applied to the corresponding copper-clad laminate can meet customized specifications. For example, by changing the corresponding number of hydroxyl groups, the glass transition temperature can be correspondingly changed (for example, the number of hydroxyl groups per molecule and the glass transition temperature are basically positively related). For example, the smaller the molecular weight, the higher the fluidity may be. As another example, the higher the molecular weight, the higher the corresponding peel strength may be. [Industrial Applicability]

[0234] In addition, the modified polyphenylene ether resin in the above-mentioned embodiment of the present invention can be directly or indirectly applied to copper-clad laminates, and further processed into other electronic components or electronic products (e.g., circuit boards or copper-clad laminates) for use in life, industry, or other suitable applications. [Explanation of symbols]

[0235] S10, S20, S30, S40 steps

Claims

1. Providing an unmodified polyphenylene ether; reacting the unmodified polyphenylene ether with a phenolic compound and a radical initiator to obtain a corresponding product; purifying the product by alkali washing and solvent recrystallization to obtain a modified polyphenylene ether resin; A method for producing a modified polyphenylene ether resin comprising the steps of:

2. 2. The method for producing a modified polyphenylene ether resin according to claim 1, wherein the unmodified polyphenylene ether comprises poly(2,6-dimethyl-1,4-phenylene ether).

3. 2. The method for preparing a modified polyphenylene ether resin according to claim 1, wherein the equivalent weight of the radical initiator is about 0.05 to about 2 times the phenol equivalent weight of the phenol compound.

4. 2. The method for producing a modified polyphenylene ether resin according to claim 1, further comprising adding a catalyst when reacting the unmodified polyphenylene ether with the phenol compound and the radical initiator.

5. It has a structure represented by the following formula (1): 【Chemistry 1】 In formula (1), k is an integer equal to or greater than 0; i, i', j, and j' are the same or different, i and j are each an integer from 0 to 200, and i' and j' are each an integer from 1 to 200; the value of i+i'+j+j'+k is between 2 and 400; R 1 ~R 8 are the same or different and are each selected from a hydrogen group or a C1-C6 alkyl group; P 1 ~P 4 are the same or different and are each selected from a single bond or a ketone group; Q 1 ~Q 4 are the same or different and are each selected from a benzene ring group, a styryl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthalene ring group, or hydrogen; X is a single bond or a linking group selected from the following chemical formulas: 【Chemistry 2】 Modified polyphenylene ether resin.

6. Providing an unmodified polyphenylene ether; reacting the unmodified polyphenylene ether with a phenolic compound and a radical initiator to obtain a corresponding product; purifying the product by alkali washing and solvent recrystallization to obtain the modified polyphenylene ether resin; The modified polyphenylene ether resin according to claim 5 , which is produced by a production method comprising the steps of:

7. The number average molecular weight is between 500 g / mol and 4000 g / mol; A molecular weight distribution of 2.5 or less; the total weight of compositions having a molecular weight greater than 20,000 g / mol accounts for less than 1.5 wt %, based on the total weight of the modified polyphenylene ether resin; The modified polyphenylene ether resin according to claim 5, having the formula:

8. 6. The modified polyphenylene ether resin according to claim 5, wherein the average number of hydroxyl groups per molecule is 2.2 or more.

9. The modified polyphenylene ether resin has a structure represented by the following formula (1): 【Chemistry 3】 In formula (1), k is an integer equal to or greater than 0; i, i', j, and j' are the same or different, i and j are each an integer from 0 to 200, and i' and j' are each an integer from 1 to 200; the value of i+i'+j+j'+k is between 2 and 400; R 1 ~R 8 are the same or different and are each selected from a hydrogen group or a C1-C6 alkyl group; P 1 ~P 4 are the same or different and are each selected from a single bond or a ketone group; Q 1 ~Q 4 are the same or different and are each selected from a benzene ring group, a styryl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthalene ring group, or hydrogen; X is a single bond or a linking group selected from the following chemical formulas: 【Chemistry 4】 Resin composition.

10. The film layer is formed from a resin composition containing a modified polyphenylene ether resin having a structure represented by the following formula (1): 【Chemistry 5】 In formula (1), k is an integer equal to or greater than 0; i, i', j, and j' are the same or different, i and j are each an integer from 0 to 200, and i' and j' are each an integer from 1 to 200; the value of i+i'+j+j'+k is between 2 and 400; R 1 ~R 8 are the same or different and are each selected from a hydrogen group or a C1-C6 alkyl group; P 1 ~P 4 are the same or different and are each selected from a single bond or a ketone group; Q1 to Q 4 are the same or different and are each selected from a benzene ring group, a styryl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthalene ring group, or hydrogen; X is a single bond or a linking group selected from the following chemical formulas: 【Chemistry 6】 Electronic components.

Citation Information

Patent Citations

  • Polyphenylene oxide resin for copper-clad plates

    CN107163244A

  • Epoxidized polyphenylene ether resin and method for manufacturing the same

    JP2009046631A

  • Phosphorous-containing functionalized poly(arylene ether) and compositions prepared therefrom

    JP2016089178A

  • Polyphenylene ether, polyphenylene ether composition, curable composition, and method for producing polyphenylene ether

    JP2019172917A

  • Process for producing low-molecular polyphenylene ether

    WO2007097231A1

Cited By

  • Resin composition

    JP2025171898A